2020
DOI: 10.1039/d0cp04376a
|View full text |Cite|
|
Sign up to set email alerts
|

Local structure of a highly concentrated NaClO4 aqueous solution-type electrolyte for sodium ion batteries

Abstract: Aqueous Na-ion batteries with highly concentrated NaClO4 aq. electrolytes are drawing attention as candidates for large-scale rechargeable batteries with a high safety level. However, the detailed mechanism by which the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 25 publications
4
50
0
Order By: Relevance
“…[2][3][4] Nonetheless, the cost-effectiveness of lithium extraction in the earth's crust and the vulnerability it brings to projects in different countries have increased the attention of the scientific community. [4][5][6] In this context, alternative technological strategies include the development of Na-ion batteries due to sodium abundance and highperformance aqueous-based supercapacitors which are more environmentally friendly compared to the traditional organicbased devices using toxic solvents. 6,7 In addition, aqueousbased supercapacitors are an attractive technology due to high ionic conductivity, which decreases the equivalent series resistance (R ESR ), and the non-flammability characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Nonetheless, the cost-effectiveness of lithium extraction in the earth's crust and the vulnerability it brings to projects in different countries have increased the attention of the scientific community. [4][5][6] In this context, alternative technological strategies include the development of Na-ion batteries due to sodium abundance and highperformance aqueous-based supercapacitors which are more environmentally friendly compared to the traditional organicbased devices using toxic solvents. 6,7 In addition, aqueousbased supercapacitors are an attractive technology due to high ionic conductivity, which decreases the equivalent series resistance (R ESR ), and the non-flammability characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…1 The major drawback regarding the use of aqueous-based supercapacitors is the reduced working voltage window (or electrochemical stability window -ESW) that limits the specific energy E = CU 2 /2, where C is the specific capacitance and U = ESW. 5,8,9 Several research groups have reported that highly concentrated aqueous-based electrolytes, especially water-in-salt electrolytes (WiSE), can mitigate the low energy limitation since the ESW values can be increased by manipulating the electrolyte properties. 5,8,10,11 Conventional electrolytes (salt-in-water electrolytes, SiWE) used traditionally in energy storage devices have concentrations in the range of B1 to 2mol dm À3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2c compared Walden plots of NaTFA aqueous electrolytes with those for representative aqueous electrolytes. 28,[34][35][36] Aqueous NaTFA over a range of 1m to 26 m may be categorized as good ionic solution, since they positioned just beneath the ideal KCl line and approached asymptotically to W = 0.1 region as the concentration increased (W: deviation).…”
Section: Resultsmentioning
confidence: 99%
“…21,22 These results prompted us to disclose our study on a concentrated aqueous sodium trifluoroacetate (NaTFA) electrolyte (26 mol kg -1 (m)), which may provide greater benefits on the symmetrical aqueous sodium-ion battery using NVTP. Since our initial reports, [26][27][28] saturated (~17 m or ~10 M (mol dm -3 )) NaClO4 electrolyte that has been used frequently in the emerging aqueous sodium-ion batteries. 22,[29][30][31] However, 26 m NaTFA electrolyte is less acidic and it has smaller mole fraction of water, which can be expected to exert a better "water-in-salt" effect.…”
Section: Introductionmentioning
confidence: 99%